Antibody Afucosylation Augments CD16-Mediated Serial Killing and IFNγ Secretion by Human Natural Killer Cells - Karampatzakis, Alexandros; Brož, Petr; Rey, Camille; Önfelt, Björn; Cruz De Matos, Gabriela Dos Santos; Rycroft, Daniel; Ambrose, Ashley; Davis, Daniel M. (Frontiers in Immunology, 2021)
One mechanism by which monoclonal antibodies (mAb) help treat cancer or autoimmune disease is through triggering antibody-dependent cellular cytotoxicity (ADCC) via CD16 on Natural Killer (NK) cells. Afucosylation is known to increase the affinity of mAbs for CD16 on NK cells and here, we set out to assess how mAb afucosylation affects the dynamics of NK cell interactions, receptor expression and effector functions. An IgG1 version of a clinically important anti-CD20 mAb was compared to its afucosylated counterpart (anti-CD20-AF). Opsonisation of CD20-expressing target cells, 721.221 or Daudi, with anti-CD20-AF increased NK cell cytotoxicity and IFNγ secretion, compared to anti-CD20. The afucosylated mAb also caused a more rapid and greater loss of CD16 from NK cell surfaces. Loss of CD16 has recently been shown to be important for NK cell detachment and sequential engagement of multiple target cells. Here, live-cell time-lapse microscopy of cell-cell interactions in an aqueous environment and a three-dimensional matrix, revealed that anti-CD20-AF induced more rapid killing of opsonised target cells. In addition, NK cells detached more quickly from target cells opsonised with anti-CD20-AF compared to anti-CD20, which increased serial engagement and lysis of multiple targets. Thus, disassembly of the immune synapse caused by loss of cell surface CD16 is a factor determining the efficiency of ADCC and this can be augmented with antibody afucosylation.